2012
DOI: 10.1007/s10646-012-0926-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals on the expression of a zinc-inducible metallothionein-III gene and antioxidant enzyme activities in Crassostrea gigas

Abstract: Sequestration by metallothioneins and antioxidant defense are two kinds of important defense mechanisms employed by mollusks to minimize adverse effects caused by heavy metal contaminants in marine environment. In the present study, a novel metallothionein gene, CgMT-III, was cloned from Crassostrea gigas, consisting of eighteen conserved cysteine residues and encoding a MT III-like protein with two tandem b domains. The expression level of CgMT-III transcript induced by zinc was much higher than that induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 72 publications
3
8
0
Order By: Relevance
“…In mollusks, several MTFs and MREs were identified; for example, three MREs were found in CvMT‐I/II and CvMT‐IV (Jenny et al ), and two MTFs in oyster, Crassostrea gigas (Qiu et al ). These studies together with other reports revealed the diversity of metal inducibility and expression pattern in different mollusk MT isoforms (Amiard et al ; Jenny et al ; Cong et al ). To further understand the multiplicity of mollusk MT function and its regulating mechanisms, more gene sequence data are required.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In mollusks, several MTFs and MREs were identified; for example, three MREs were found in CvMT‐I/II and CvMT‐IV (Jenny et al ), and two MTFs in oyster, Crassostrea gigas (Qiu et al ). These studies together with other reports revealed the diversity of metal inducibility and expression pattern in different mollusk MT isoforms (Amiard et al ; Jenny et al ; Cong et al ). To further understand the multiplicity of mollusk MT function and its regulating mechanisms, more gene sequence data are required.…”
supporting
confidence: 74%
“…Metallothionein (MT) is a low‐molecular‐weight, metal‐binding, and cysteine‐rich protein first isolated in renal cortical cells of Equus caballus (Margoshes and Vallee ). Since then, MT was identified in many organisms including aquatic invertebrate mollusks (Binz and Kägi ; Amiard et al ; Cong et al ). Based on structural relationships, MTs have been subdivided into three classes (Fowler et al ).…”
mentioning
confidence: 99%
“…The arrangement pattern of nine Cys is obviously similar with the β 2 -domain of the gastropod β 1 β 2 -MTs (Jenny et al 2006;Jenny et al 2016). The same β 2 β 2 -domain structure has also been found in C. gigas MT-III (JF781299); however unlikely in C. virginica, multiple MT-III subisoforms have not been characterized in C. gigas (Cong et al 2012). The C. gigas MT-III shows a series of substitutions of non-Cys aa from the C. virginica MT-III isoforms.…”
Section: Bivalve-ostreidae Mtsmentioning
confidence: 58%
“…Further, C. virginica MT-III represented only a moderate responsiveness to heavy metal exposures in both larvae and adults (Jenny et al 2006). However, on the contrary, the C. gigas MT-III has been reported to be significantly induced by zinc (as a main regulator for zinc homeostasis), and it may be a participating member for cadmium detoxification in the adult tissues (Cong et al 2012). Thereby, it suggests the functional differentiation/divergence of MT-III isoforms during speciation events in the Crassostrea lineage.…”
Section: Bivalve-ostreidae Mtsmentioning
confidence: 97%
“…MT1s are involved in diverse functions, such as metal homeostasis, metal donation to different enzymes, angiogenesis, apoptosis, cell differentiation, radiation cell damage as well as carcinogenesis . Given their broad regulatory properties, MT1s have also been suggested to play important roles in cell senescence and various pathological processes, such as neurodegeneration, osteoarthritis, metabolic disorders, and certain immune processes . In recent years, some postulated pathophysiological effects of MT1s have been associated with distinct functional polymorphisms of MT1 genes …”
Section: Introductionmentioning
confidence: 99%